Greater role for Atlantic inflows on sea-ice loss in the Eurasian Basin of the Arctic Ocean - Polyakov, Igor V.; Pnyushkov, Andrey V.; Alkire, Matthew B.; Ashik, Igor M.; Baumann, Till M.; Carmack, Eddy C.; Goszczko, Ilona; Guthrie, John; Ivanov, Vladimir V.; Kanzow, Torsten; Krishfield, Richard; Kwok, Ronald; et al. (Science (American Association for the Advancement of Science), 2017)
Arctic sea-ice loss is a leading indicator of climate change and can be attributed, in large part, to atmospheric forcing. Here, we show that recent ice reductions, weakening of the halocline, and shoaling of the intermediate-depth Atlantic Water layer in the eastern Eurasian Basin have increased winter ventilation in the ocean interior, making this region structurally similar to that of the western Eurasian Basin. The associated enhanced release of oceanic heat has reduced winter sea-ice formation at a rate now comparable to losses from atmospheric thermodynamic forcing, thus explaining the recent reduction in sea-ice cover in the eastern Eurasian Basin. This encroaching “atlantification” of the Eurasian Basin represents an essential step toward a new Arctic climate state, with a substantially greater role for Atlantic inflows.